A cautionary tale for health education initiatives in vulnerable populations: Improving nutrition in Haiti prisons - Mainous, Arch G.; Bernard, Jean; Auguste, Stephanie; Louis, Jacques R.; Dieufort, Danove J.; Duverger, Karine; Beau de Rochars, Madsen; May, John (Frontiers in Medicine, 2022)
Introduction Prisons in low income countries have barriers to providing adequate nutrition to the incarcerated men. This perspective discusses a quality improvement program with health education to improve nutrition provided to men in two prisons in Haiti. Methods Incarcerated men in the National Penitentiary in Port Au Prince and the prison in Mirebalais were the focus of the program. A culturally competent educational intervention was delivered to the prison cooks. Program evaluation included a baseline and a follow-up assessment in 2021 and 2022 in both prisons. Calories, body composition and nutrition were assessed at both time points. Results Among 1060 men assessed in the baseline time period, the mean number of calories per day was 571. Further, 62.5% had a vitamin C intake insufficient to prevent scurvy and 91.6% had vitamin B1 insufficient to prevent beriberi. In the follow-up period, caloric intake decreased to a mean of 454 per day (p<.001). The proportion of incarcerated men who had insufficient vitamin C and vitamin B1 to prevent disease increased in the follow-up period. Discussion The caloric and nutritional intake of incarcerated men in Haitian prisons is poor and is getting worse. The educational intervention with the cooks was not successful due to civil and political strife in the low-income country of Haiti. Standard interventions to improve nutrition need to consider the social context for accessing food.